قراءة نقدية في مصطلح الثورة - الهادي, عامر (University of Eloued جامعة الوادي, 2021)
يحاول المقال معالجة الأدبيات المتنوعة المتعلقة بمصطلح ''الثورة''، وهو المصطلح الذي حاز اهتمام ورعاية كبيرين من لدن الباحثين في حقول العلم المختلفة وعلى وجه الخصوص في حقلي السياسة والعلوم الإنسانية. إلا أننا في هذه الدراسة حولنا التوسع وكسر الحدود التقليدية والكلاسيكية للتوسع أكثر فأكثر إلى الحقول الأخرى، مع التركيز على الأدبيات الغربية كونها كانت سابقة في العديد من الثورات على مختلف الأصعدة في التاريخين الحديث والمعاصر. The article aims to study the various literature related to the term `` revolution, '' which is a term that has gained great interest and patronage among researchers in the various fields of science, especially in the fields of politics and the humanities. However, in this study, we shifted the expansion and broke the traditional and classic boundaries to expand more and more to other fields, with a focus on Western literature as it was precedent in many revolutions at various levels in the modern and contemporary history.
مقال